Proton Magnetic Resonance Spectroscopy in Common Dementias—Current Status and Perspectives - Maul, Stephan; Giegling, Ina; Rujescu, Dan (Frontiers in Psychiatry, 2020)
Dementia occurs mainly in the elderly and is associated with cognitive decline and impairment of activities of daily living. The most common forms of dementia are Alzheimer's disease (AD), vascular dementia (VD), dementia with Lewy bodies (DLB) and frontotemporal dementia (FTD). To date, there are no causal options for therapy, but drug and non-drug treatments can positively modulate the course of the disease. Valid biomarkers are needed for the earliest possible and reliable diagnosis, but so far, such biomarkers have only been established for AD and require invasive and expensive procedures. In this context, proton magnetic resonance spectroscopy (1H-MRS) provides a non-invasive and widely available technique for investigating the biochemical milieu of brain tissue in vivo. Numerous studies have been conducted for AD, but for VD, DLB and FTD the number of studies is limited. Nevertheless, MRS can detect measurable metabolic alterations in common dementias. However, most of the studies conducted are too heterogeneous to assess the potential use of MRS technology in clinical applications. In the future, technological advances may increase the value of MRS in dementia diagnosis and treatment. This review summarizes the results of MRS studies conducted in common dementias and discusses the reasons for the lack of transfer into clinical routine.